Surface Roughness Analysis on the Dry Turning of an Al-Cu Alloy. (2015) - Torres, A.; Puertas, I.; Luis, C.J.
Abstract: Nowadays, surface finish has become an important indicator of quality and precision in manufacturing processes and it is considered one of the most important parameter in Industry. In this present study, the influence of different machining parameters on surface roughness has been analyzed. All these parameters have been studied in terms of depth of cut (ap ), feed rate (F), cutting speed (Vc ) and tool radius (R). A 2030-T4 aluminium alloy has been selected. Moreover, Design of Experiments (DOE) techniques have been used to predict the surface quality in advance and to select the optimal turning conditions. The experimental results revealed that for dry turning operations and for the amplitude parameters, the most significant factor was the interaction effect between the depth of cut and the feed rate. In addition, for facing operations, the feed rate turned out to be the most statistically influential factor of all the surface roughness parameters.